2021
DOI: 10.1007/s40121-021-00406-w
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Conjugate Vaccine Impact on Serotype 3: A Review of Surveillance Data

Abstract: Introduction Limited changes in serotype 3 invasive pneumococcal disease (IPD) incidence rates after a decade of 13-valent pneumococcal conjugate vaccine (PCV13) introduction into several national immunization programs (NIP) have raised questions about PCV13's effectiveness against this serotype. Methods We analyzed the impact of pediatric PCV programs on serotype 3 IPD with two approaches. First, we reviewed the publicly available surveillance data from countries ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…All these results seem to support the lower effectiveness of PCV13 against serotype 3 complicated pneumonia, although unexplained geographical differences persist [ 29 ]. The reasons behind these differences could be related to different vaccination schedules, risk factors, natural trends, differences in sampling or transmission dynamics, as already suggested to account for other differences in serotype replacement [ 29 , 30 ]. Differences in the etiologic diagnosis methods could potentially further affect the results since the use of molecular methods to complement culture is essential to avoid underestimating this important serotype in the epidemiology of pIPD.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…All these results seem to support the lower effectiveness of PCV13 against serotype 3 complicated pneumonia, although unexplained geographical differences persist [ 29 ]. The reasons behind these differences could be related to different vaccination schedules, risk factors, natural trends, differences in sampling or transmission dynamics, as already suggested to account for other differences in serotype replacement [ 29 , 30 ]. Differences in the etiologic diagnosis methods could potentially further affect the results since the use of molecular methods to complement culture is essential to avoid underestimating this important serotype in the epidemiology of pIPD.…”
Section: Discussionmentioning
confidence: 90%
“…In Germany, after the introduction of PCV13, and in a situation of high vaccination coverage, serotype 3 pneumonia with parapneumonic pleural effusion or empyema increased and a considerable number of vaccine failures were associated with this serotype [11]. All these results seem to support the lower effectiveness of PCV13 against serotype 3 complicated pneumonia, although unexplained geographical differences persist [29]. The reasons behind these differences could be related to different vaccination schedules, risk factors, natural trends, differences in sampling or transmission dynamics, as already suggested to account for other differences in serotype replacement [29,30].…”
Section: Discussionmentioning
confidence: 91%
“…Totality of Data Are Consistent with PCV13 Efficacy against Serotype 3 Similar to the Overall PCV13 Efficacy PCV13 has been introduced into pediatric national immunization programs in many countries globally with high uptake and in the USA and other countries also with programs targeting older adults [34,35]. Nevertheless, serotype 3 continues to be among the most prevalent serotypes causing IPD in adults [36][37][38][39]. This raises the question of whether PCV13 has limited ability to reduce serotype 3 carriage (and thus provide indirect protection), limited ability to provide direct protection against this serotype in vaccinated persons, or both.…”
Section: The Trial Demonstrated Pcv13 Protection Up To 84 Years Of Ag...mentioning
confidence: 99%
“…Although this may indicate that PCV13 may provide better protection, empirical data has shown that PCV13 has little to no protection against serotype 3 and has similar levels of serotype replacement as PCV10. (39,40) This higher predictions in serotype coverage for PCV13 may therefore not translate to larger IPD reductions. Our predictions show that SII-PCV has similar coverage to PCV10, and we attribute this to differences in carriage prevalence and IC of the included and excluded serotypes.…”
Section: Discussionmentioning
confidence: 99%